COVID-19 vaccine inequity in African low-income countries - Kunyenje, Chifundo Annessia; Chirwa, Gowokani Chijere; Mboma, Sebastian M.; Ng'ambi, Wingston; Mnjowe, Emmanuel; Nkhoma, Dominic; Ngwira, Lucky Gift; Chawani, Marlen Stacey; Chilima, Ben; Mitambo, Collins; Crampin, Amelia; Mfutso-Bengo, Joseph (Frontiers in Public Health, 2023)
Equitable access and utilization of the COVID-19 vaccine is the main exit strategy from the pandemic. This paper used proceedings from the Second Extraordinary Think-Tank conference, which was held by the Health Economics and Policy Unit at the Kamuzu University of Health Sciences in collaboration with the Malawi Ministry of Health, complemented by a review of literature. We found disparities in COVID-19 vaccine coverage among low-income countries. This is also the case among high income countries. The disparities are driven mainly by insufficient supply, inequitable distribution, limited production of the vaccine in low-income countries, weak health systems, high vaccine hesitancy, and vaccine misconceptions. COVID-19 vaccine inequity continues to affect the entire world with the ongoing risks of emergence of new COVID-19 variants, increased morbidity and mortality and social and economic disruptions. In order to reduce the COVID-19 vaccination inequality in low-income countries, there is need to expand COVAX facility, waive intellectual property rights, transform knowledge and technology acquired into vaccines, and conduct mass COVID-19 vaccination campaigns.